Improving Medication Adherence in Geriatric T2DM Patients: A Factorial Randomized Controlled Trial - Shambo Samrat Samajdar; Rohan Tripathi; Shatavisa Mukherjee; Kaushik Biswas; Shashank R Joshi; Sougata Sarkar; Santanu K Tripathi; Bharat Saboo (Journal of Diabetology)
Background: The complexity of managing type 2 diabetes (T2D) in the elderly is compounded by the need to balance over-prescription, under-prescription, and appropriate prescription. Managing hyperglycemia and its complications, along with geriatric syndromes such as cognitive impairment and falls, often leads to use of an increased number of medications. Quality improvement measures, while aimed at better management, can inadvertently contribute to the burden of polypharmacy. Addressing medication non-adherence is crucial, as it is a significant contributor to poor clinical outcomes, increased hospitalizations, and healthcare costs.